Impact of trunk muscle and neuromuscular fatigue on knee muscle feedforward activation and postural control in elite female athletes: a cross-sectional crossover study - Seifali, S.; Gandomi, F.; Maffulli, N. (Sport Sciences for Health, 2026)
Background and aims The core plays a crucial role in providing stability, facilitating efficient force transmission, and reducing the risk of injury in athletes. Core muscle fatigue can disrupt neuromuscular function, potentially impairing knee joint control and postural stability. This study examined the effects of trunk muscle and neuromuscular fatigue on knee muscle feedforward activation and postural control in elite athletes.